A comparison of toxicity profile of gemcitabine monotherapy versus etoposide/cisplatin in the treatment of locally advanced or metastatic non-small cell lung cancer - Prakash, Ved; Singh, Arpita; Kant, Surya; Verma, Ajay K.; Saxena, Prachi; Bhatia, Ankit (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Lung cancer is the leading cause of cancer deaths globally in which about 40% patients reporting in advanced stage disease. Both platinum and non platinumcombinations have been shown to be equally efficacious as initial first-line treatment of advanced non-small cell lung cancer (NSCLC), however because of the toxicity of cisplatin, combination treatment can only be administered to a minority of patients in good general health. Gemcitabine could be combined with one of the other new agents to create novel non-platinum-doublet combinations with efficacy and/or toxicity profile superior to that of standard platinum based combinations. Hence, this study was conducted to compare the toxicity profiles of gemcitabine monotherapy and the cisplatin/etoposide combination therapy. Methods: This was a randomized prospective study, which included 96 patients selected on the basis of histologically or cytologically confirmed Stage III B or IV of NSCLC. Study was divided into two arms-Arm A received gemcitabine monotherapy in a dose of 1000 mg/m2 on day 1 and 5 of the cycle andrepeated after every 3 weeks while Arm B received cisplatin (25 mg/m2 on day 1, 2 and 3) + etoposide (100 mg/m2). Patient were evaluated for adverse events by following World Health Organization grading of toxicity. Results: Out of the 96 patients enrolled in the study, 74 (77.0%) patients were eligible and were analyzed. Of these, 36 (37.5%) patients belonged to Arm A and 38 (39.5%) to Arm B. Transient vomiting (45.8% vs. 37.5%), leukopenia (33.3% vs. 8.3%) were seen more in Arm A, while thrombocytopenia (33.3% vs. 12.5%), patchy hair loss (68.4% vs. 16.6%) was seen more in Arm B. Nephrotoxicity was seen almost similarly in both the groups. Conclusions: Single-agent gemcitabine appears to have a safer toxicity profile than the combination cisplatin-etoposide in the first-line chemotherapy of advanced NSCLC. With less toxic anticancer drugs like gemcitabine, the physician now has greater choice in choosing treatment, which can have better effect on the patients concerned.